DISTRIBUTION MODEL OF HUMAN DEVELOPMENT INDEX IN PAPUA PROVINCE BASED ON REGIONAL CLUSTERING - Wororomi, Jonathan K.; Sroyer, Alvian M.; Morin, Henderina; Reba, Felix; Beno, Ishak S.; Wambrauw, Oscar O. O. (PATTIMURA UNIVERSITY, 2025)
Modeling the distribution of Human Development Index (HDI) components is essential to uncover underlying disparities and guide targeted policy interventions. This study aims to analyze HDI data, focusing on the average length of schooling across 26 districts in Papua Province from 2010 to 2023, to identify the most suitable probability distribution model. Using the k-means clustering method, two main groups were identified based on the average length of schooling. Cluster 1 includes 11 districts with a Weibull distribution, characterized by a scale parameter of 8.9931 and a shape parameter of 16.1272, indicating significant variation in education duration. Cluster 2 consists of 15 districts with a scale parameter of 3.73006 and a shape parameter of 8.07662, showing a distribution with a long tail and greater variability. This study provides insights into the distribution patterns of education duration in Papua, which could aid policymakers in making more targeted decisions and allocating resources efficiently. The findings also highlight regional disparities and the need for specific educational interventions. These results are valuable for government entities, NGOs, researchers, and international donors interested in improving educational outcomes in underdeveloped areas. However, the analysis is limited by the scope of available data and the assumption of homogeneity within clusters.